Efektifitas Manajemen Promosi Media Sosial terhadap Penerimaan Mahasiswa Baru UNMER Madiun - Agnyana, Handaru; Rafsanjani Akbar, Salma; Setivia Bakti, Nurimansyah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
The development of promotional media has now entered the digital era that can communicate promotions more widely and quickly. In Indonesia, the phenomenon of online media that is anticipated to replace print media also continues to increase. As done by the New Student Admissions Team (PMB) of Merdeka Madiun University in accepting new students, they provide information about many things, such as registration procedures, achievements, and what can be obtained when registering for the campus. Various methods used by them, one of which is by conveying information through advertisements. Through this advertisement, the PMB Team promotes the university to the public. The purpose of making the advertisement is so that the public obtains information and is interested in following and trying what is advertised, namely doing or registering themselves related to what is being advertised. Advertisements use language that is easy to understand and persuasive to attract people who see it. In addition, advertisements are made using video and sound visualizations that are packaged very attractively according to the target market to be achieved, namely prospective new students who are included in generation Z and generation alpha.